2021
DOI: 10.3390/ma14185201
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Effect of Phase Composition and Transformation on the Mechanical Properties of a Cu–6Ni–6Sn–0.6Si Alloy

Abstract: In the present study, a Cu–6Ni–6Sn–0.6Si alloy is fabricated through frequency induction melting, then subjected to solution treatment, rolling, and annealing. The phase composition, microstructure evolution, and transition mechanism of the Cu–6Ni–6Sn–0.6Si alloy are researched systematically through simulation calculation and experimental characterization. The ultimate as-annealed sample simultaneously performs with high strength and good ductility according to the uniaxial tensile test results at room temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…On the one hand, adding some micro-alloying elements (Cr, Si, Al, Ti, Co, Fe and Nb) can inhibit the grain growth during heat treatment, and improve organization and performance [19][20][21][22][23][24]. On the other hand, the second phase particles can also be introduced at grain boundaries to inhibit the formation of DP, so as to maintain mechanical properties of the alloy [25,26]. For example, Guo et al showed that adding Fe element into Cu-15Ni-8Sn alloy can improve the aging resistance and mechanical properties of the alloy [27].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, adding some micro-alloying elements (Cr, Si, Al, Ti, Co, Fe and Nb) can inhibit the grain growth during heat treatment, and improve organization and performance [19][20][21][22][23][24]. On the other hand, the second phase particles can also be introduced at grain boundaries to inhibit the formation of DP, so as to maintain mechanical properties of the alloy [25,26]. For example, Guo et al showed that adding Fe element into Cu-15Ni-8Sn alloy can improve the aging resistance and mechanical properties of the alloy [27].…”
Section: Introductionmentioning
confidence: 99%